Low grade nasopharyngeal papillary adenocarcinoma case report from the Middle East - Mohammed, Suzan S.; Ahmad, Hassan H.; Ammar, Adham A.; Rahman, Waheed (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Nasopharyngeal papillary adenocarcinoma variety is extremely rare type of nasopharyngeal carcinoma. Limited number of cases reported in the literature, with most cases being reported from west and south Asia. We report the first case in English literature from the middle east and south Africa. A young gentleman diagnosed with low-grade nasopharyngeal papillary adenocarcinoma with positive cervical lymph node. He received a combined approach with endoscopic resection of the lesion and concomitant Left neck dissection followed by planned chemoradiotherapy. Through this case report, we would like to share our treatment approach and explore the optimum therapeutic strategies for primary nasopharyngeal papillary adenocarcinomas.